The Handling Of Hoax/False Information In The Legal Jurisdiction Area - Nur Cahyo Ari Prasetyo; Sri Endah Wahyuningsih (Law Development Journal, 2021)
This study aims to identify and analyze the handling of hoaxes in the jurisdiction of the Central Java Regional Police and the obstacles faced in handling hoaxes in the jurisdiction of the Central Java Regional Police. The approach method used is sociological juridical, descriptive analytical research specifications, types and sources of data using primary and secondary data, data collection methods are field studies and literature studies, while the data analysis method uses qualitative analysis. The results showed that phandling hoaxes in the jurisdiction of the Central Java Regional Police through preemptive, preventive and repressive efforts which are the last resort. The handling of hoaxes at the Central Java Regional Police is in line with progressive legal theory which is based on the principle that the law is for humans. In handling hoaxes, there are several obstacles faced, namely the difficulty of finding perpetrators, difficulties in uncovering evidence, the lack of facilities and infrastructure, the budget required for handling hoaxes is very large, differences in legal perspectives from the founding countries of social media. These obstacles are an inhibiting factor in law enforcement.